Analisis Faktor-Faktor Penentu Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Pasar Desa Bojongkulur, Bogor - Hero Wirasmara Kusuma; Suhroji Adha; Didi Wandi (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research is entitled "Analysis of Determining Factors of Service Quality on Consumer Satisfaction at the Bojongkulur Village Market, Bogor". The aim of the research is to determine the significant positive influence simultaneously and partially between the independent variables, namely service quality consisting of physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) towards the dependent variable, namely customer satisfaction (Y) at the Bojongkulur Village Market. The population in this study were consumers at the Bojongkulur Village Market. Furthermore, the sampling technique used in this research was "Simple Random Sampling" where respondents were shopping at the Bojongkulur Village Market. Data collection was carried out using a questionnaire technique. The results of this research are; (1)Simultaneously, service quality (physical evidence, reliability, responsiveness, assurance and empathy) has a positive, strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 63%. (2)Partially, physical evidence has a positive, quite strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 54%. (3)Partially, reliability has a positive, quite strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 58%. (4)Partially, responsiveness has a positive, relatively strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 60%. (5)Partially, guarantees have a positive, strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 62%. (6)Partially, empathy has a positive, quite strong and significant effect on consumer satisfaction at the Bojongkulur Village Market. This is shown by the R-Square gain of 52%.